Improvement of water preparation technology in the production of rye beer - Dulka, Olha; Prybylskyi, Vitalii; Oliynyk, Svitlana (My University, 2016)
This research explores the effect of filtering and sorption materials (clinoptilolite, active coal, and rock crystal) on the basic organoleptic and physico-chemical properties of water. It was established that the water processed with the explored materials in the sequence clinoptilolite, activated charcoal, rhinestone significantly improves the organoleptic properties of rye beer. Herewith rye beer on the prepared water was transparent, with a typical dark brown color, without impurities, with soft and harmonious sweet and sour taste and pleasant flavor.
Keywords: водопідготовка; органолептичні властивості; клиноптилоліт; активне вугілля; мінерали; пиво житнє; water; water preparation; organoleptic propertie; кафедра біотехнології продуктів бродіння і виноробства